2017
DOI: 10.19084/rca16118
|View full text |Cite
|
Sign up to set email alerts
|

Drought tolerance of wheat and black oat crops at early stages of seedling growth

Abstract: A B S T R A C TSeeds of wheat (Triticum aestivum L., cv. Jadeíte 11) and black oat (Avena strigosa Schreb., cv. Agro Planalto) were submitted to different osmotic potential levels induced by polyethylene glycol (PEG) with the objective of evaluate the effects of drought stress on seed germination and early seedling growth. Seeds were arranged in paper rolls and soaked in PEG solutions prepared with osmotic potentials from 0.0 (control), -0.2, -0.4, and -0.8 MPa and kept into a seed germinator, at 25°C for 15 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 19 publications
1
20
0
4
Order By: Relevance
“…These results suggest that the start of the seed germination process was delayed under water and saline stress conditions, when compared to the seeds under non-stressful control conditions. The delay of the germination process in stressful environments has been commonly reported for other crops, such as soybean (Pereira et al 2013, Soares et al 2015, common bean (Coelho et al 2010), naked oat (Mut & Akay 2010) and wheat (Shahi et al 2015, Steiner et al 2017).…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…These results suggest that the start of the seed germination process was delayed under water and saline stress conditions, when compared to the seeds under non-stressful control conditions. The delay of the germination process in stressful environments has been commonly reported for other crops, such as soybean (Pereira et al 2013, Soares et al 2015, common bean (Coelho et al 2010), naked oat (Mut & Akay 2010) and wheat (Shahi et al 2015, Steiner et al 2017).…”
Section: Resultsmentioning
confidence: 84%
“…Several studies have shown that the shoot is more likely to be affected by abiotic stresses than other traits (Mut & Akay 2010, Shahi et al 2015, Steiner et al 2017. The highest root growth of peanuts observed under drought conditions must have occurred as a response of the plant to adverse conditions of the medium.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A germinação das sementes é a primeira e a fase mais sensível e crítica para o ciclo de vida das plantas, e o estresse hídrico é o principal fator ambiental que restringe o adequado estabelecimento das culturas (PETROVIC et al, 2016;STEINER et al, 2017;QUEIROZ et al, 2019 Muitos fatores podem afetar as respostas das plantas ao estresse hídrico como genótipo e espécies de planta, estádio de crescimento, severidade e duração do estresse, dentre outros fatores ambientais (PATANÈ et al, 2013;PETROVIC et al, 2016;QUEIROZ et al, 2019). Diferenças genéticas na tolerância à estresses abióticos em condições de cultivo protegido têm sido reportadas em cultivares de soja brasileiras (ZOZ et al, 2013) As sementes foram previamente esterilizadas com hipoclorito de sódio 1% (v/v) durante 10 minutos, e então lavadas em água corrente e colocadas para germinar sob condições de estresse hídrico induzido por solução com potencial osmótico de -0,30 MPa preparada com polietilenoglicol (PEG-6000).…”
Section: Taxas Faixa Etáriaunclassified